Multi-Cutting Improves Forage Yield and Nutritional Value and Maintains the Soil Nutrient Balance in a Rainfed Agroecosystem - Li, Tengfei; Peng, Luxi; Wang, Hua; Zhang, Yu; Wang, Yingxin; Cheng, Yunxiang; Hou, Fujiang (Frontiers in Plant Science, 2022)
To explore the effects of simulated grazing (SG) and hay harvesting (H) on the productivity and soil nutrient dynamics of different forage varieties, the yield, nutrient quality, and soil nutrient contents of monoculture (Vicia sativa, Avena sativa) and mixed sowing (Vicia sativa + Avena sativa) cultivated grassland on the Loess Plateau were measured. The results show that (1) SG could increase forage yield, crude protein, and crude fat content and decrease crude ash content. In 2014, the yield of Avena sativa per hectare was 3,578.11 kg higher than that of H; (2) the model analysis for predicting nutritional components showed that the CP and EE contents of forages in each variety (combination) showed a linear downward trend with increasing forage yield; (3) Redundancy analysis (RDA) showed that precipitation, especially in the growing season, was positively correlated with grass yield and CP content; (4) there were significant differences in soil organic carbon, total nitrogen, NO3--N, and NH4+-N contents for the different forage varieties (combinations) under different use modes; the values first decreased, then increased, and finally decreased. According to the comprehensive evaluation value calculated by Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS), mixed sowing was better than monoculture, and SG obtained better results than H. Overall, mixed sowing under SG can improve forage yield and nutritional quality. At the same time, precipitation regulation is the key factor affecting the production performance of rainfed cultivated grassland on the Loess Plateau.